Comparative Study of Physicochemical Properties and Metal Contents in Crude Oil from Different Fields in Iraq - AlGburi, Ahmed Abdulrazzaq Hadi; Vikram Rama Uttam Pandit,; Ali Khalil kadom,; Talib Mohammed Albayati, (University of Thi-Qar Journal of Science, 2024)
This research evaluates the physical and chemical properties and concentration of trace elements and heavy metals in Iraqi crude oil. The way in which geographical locations affect oil quality is not widely known, especially in the Middle East. Therefore, crude oils from three locations (East Baghdad, Khurmala, and Nahr Omar) were selected. The physical and chemical data showed apparent variations in the properties of crude oils from different fields. Nahr Umr oil was the lightest (D = 0.8199 g/cm3, API = 40.57°) and the lowest in sulfur content (1.327 wt%), East Baghdad oil was the heaviest (D = 0.9067 g/cm3, API = 24.39°) and the highest in sulfur content (3.842 wt%), while Khurmala  was (D = 0.8518 g/cm3, API = 34.12°) and (2.44 wt%) of sulfur content, reflecting the differences in the quality of crude oils. Advanced techniques such as the rotating disc electrode optical emission spectrometer (RDE-OES) and inductively coupled plasma (ICP-OES/MS) were used to measure the element content after sample preparation using microwave acid digestion. The content of metals in crude oil indicates that East Baghdad oil contains the highest rate of V, Al, Ag, and Hg. At the same time, Ni, Fe, Na, Ca, Pb, Se, and Li were higher in Khurmala oil, while Mo, Ti, Sr, Bi, Ba, and Hg were higher in Nahr Umr. The statistical analysis of the least significant difference (LSD) test was used to show the significant differences between the measured element concentrations at the 0.05 level